2008
DOI: 10.1007/s10522-008-9192-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell volume as a factor limiting the replicative lifespan of the yeast Saccharomyces cerevisiae

Abstract: The number of cell divisions of the yeast Saccharomyces cerevisiae is limited, referred to as "replicative lifespan" of this organism and believed to be due to aging mechanisms similar to those of mammalian cells. We demonstrate, using three pairs of isogenic yeast strains (standard and a mutant deficient in an antioxidant defense protein) that although the lifespan differs significantly, the final volume attained after the last division is similar within each pair of strains. In a population, cells cease to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 44 publications
(38 reference statements)
5
69
0
4
Order By: Relevance
“…Thus, the simplest model would predict that large cells are short-lived predominately because they are born In addition, several recent reports support the conclusion that increasing cell size limits lifespan. 26,27,42,43,47 Conceptually similar experiments have shown that increasing the size of human or chicken fibroblasts also shortens lifespan. 9,38 In addition, a mutation in the yeast ATP2 gene that eliminates age asymmetry (e.g., daughter cells are born old) also produces abnormally large cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
See 4 more Smart Citations
“…Thus, the simplest model would predict that large cells are short-lived predominately because they are born In addition, several recent reports support the conclusion that increasing cell size limits lifespan. 26,27,42,43,47 Conceptually similar experiments have shown that increasing the size of human or chicken fibroblasts also shortens lifespan. 9,38 In addition, a mutation in the yeast ATP2 gene that eliminates age asymmetry (e.g., daughter cells are born old) also produces abnormally large cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
“…Attempts to directly determine if increasing cell size shortens longevity have had conflicting results. 20,26,27 In order to clarify this discrepancy, we used two alternative approaches to artificially enlarge the size of long-lived ssf1Δ cells. Asynchronous log-phase cultures of ssf1Δ cells are dramatically smaller (MCV 66.6 fL) and longer-lived that was independent of birth size.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 3 more Smart Citations